Tate Report : Tate Gallery Biennial Report 1992-94. - Tate Gallery, London (London : Tate Gallery, 1994)
Baselitz, Georg ; Picasso, Pablo ; Kitaj, R.B. : Fautrier, Jean ; Bomberg, David ; Whiteread, Rachel ; Richter, Gerhard ; Heron, Patrick ; Hockney, David ; Hepworth, Barbara ; Freud, Lucian ; Boltanski, Christian ; Viola, Bill ; etc.
Contents: Achievements of the Biennium ; Tate Gallery St Ives ; Tate Gallery Liverpool ; Gifts to the Collection ; Acquisitions for the Collection 1992-94 ; loans ; exhibitions ; publications ; ...
Engels
boek